2020
DOI: 10.3390/nano10061192
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Fiber Based on Natural Material for Water Disinfection under Visible Light Irradiation

Abstract: In the last decade, pathogenic bacteria and organic micropollutants have become a major issue in the water purification process. Heterogeneous photocatalysis is a low-cost and an ecofriendly process, which provides a sustainable solution for water treatment and its utilization in rural areas. In this context, we studied the generation and the surface engineering of polyacrylonitrile (PAN)/goethite composite nanofibers for photocatalytic water remediation under visible-light illumination. The photocatalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The collected solution was dropped on glass slide, stained with Gram stain, dried and observed under a microscope (MO, CL-S, Nikon, Japan) [ 28 , 35 ]. Moreover, the surface of the coating film was rinsed for 3 times with 10 mL PBS buffer, and 50 μL of the collected solution was cultured in an incubator at 37 °C for 24 h via the plate coating method [ 36 , 37 ]. The photocatalytic inactivation effect of the coating film was evaluated by calculating number of E. coli colonies.…”
Section: Methodsmentioning
confidence: 99%
“…The collected solution was dropped on glass slide, stained with Gram stain, dried and observed under a microscope (MO, CL-S, Nikon, Japan) [ 28 , 35 ]. Moreover, the surface of the coating film was rinsed for 3 times with 10 mL PBS buffer, and 50 μL of the collected solution was cultured in an incubator at 37 °C for 24 h via the plate coating method [ 36 , 37 ]. The photocatalytic inactivation effect of the coating film was evaluated by calculating number of E. coli colonies.…”
Section: Methodsmentioning
confidence: 99%
“…Water contamination is becoming a significant problem that affects all living organisms. 1,2 Numerous organic contaminants have been identified in a variety of water sources. 3 These are divided into several categories, including pesticides, fertilizers, phenols, plasticizers, detergents, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to population increases, industrialization, agriculture, and various other activities, water quality is continuously declining. Water contamination is becoming a significant problem that affects all living organisms. , Numerous organic contaminants have been identified in a variety of water sources . These are divided into several categories, including pesticides, fertilizers, phenols, plasticizers, detergents, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al [ 9 ] showed that natural-based photoactive membranes can be easily prepared by the electrospinning method. This process is especially interesting because it enables the incorporation of natural minerals such as goethite in a polymeric nanofiber structure in one step, as prepared materials showed high biological activity in photocatalytic water remediation under visible-light illumination.…”
mentioning
confidence: 99%
“…The elaborated goethite composite nanofibers showed improved photoefficiency upon dye bleaching Escherichia coli and Clostridium perfringens deactivation. Moreover, due to the specific porous structure, these materials provide a promising application in continuous flow systems [ 9 ]. Small metallic nanoparticles such as Pt, Au, or Pd are also commonly used for catalytic applications.…”
mentioning
confidence: 99%